GILIAT INFORMASI AKUNTANSI USAHA KECIL ROTAN TRANGSAN SUKOHARJO - Pardi Pardi; Nursiam Nursiam (Jurnal Akuntansi dan Pajak, 2022)
This research aimed to analyze the impact of education, number of employees, period of business, turnover and accounting learning on accounting information of small rattan enterprises. This was a quantitative research which population consisted of 194 rattan craftsmen and sample of 31 respondents. The authors used validity and normality tests on primary data from craftsmen based on questionnaires. Multiple linear regression, T test, F test, and the coefficient of determination test were used to prove the hypotheses. Partially, accounting education and learning had a material impact on accounting information. Meanwhile, the number of employees, duration of activity, and turnover did not have an impact on accounting information of small rattan enterprises. Altogether, education, number of employees, duration of activity, turnover, and accounting lessons had an impact on accounting information of small rattan business. Keywords: Analysis, Accounting Information, Small Enterprises